2021
DOI: 10.1089/bfm.2020.0259
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine Concentrations in the Breast Milk and Plasma of Nursing Mothers: Estimation of Relative Infant Dose

Abstract: Benzodiazepines are common therapies for mental illness and insomnia and are used during pregnancy and lactation. Although benzodiazepines have been shown to be transferred into breast milk, the amount transferred is small and compatible with breastfeeding. However, information is not available for all drugs. Therefore, we aimed to determine the milk to plasma (M/P) ratio and relative infant dose (RID), which are used as indicators of drug transfer to breast milk, to determine the safety of such drugs for lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Benzodiazepines are excreted in breast milk. A Japanese study of 11 nursing mothers and their 1-month-old infants taking benzodiazepines, including alprazolam, brotizolam, clonazepam, flunitrazepam, and lorazepam, among others, found that the ratio of breast milk to maternal plasma benzodiazepine level was consistently less than 1, and the relative infant dose was always less than 10% of the maternal dose except for ethyl loflazepate, which was only slightly greater than 10% [168]. No abnormalities were noted in the infants.…”
Section: Use Of Benzodiazepines In Special Circumstancesmentioning
confidence: 99%
“…Benzodiazepines are excreted in breast milk. A Japanese study of 11 nursing mothers and their 1-month-old infants taking benzodiazepines, including alprazolam, brotizolam, clonazepam, flunitrazepam, and lorazepam, among others, found that the ratio of breast milk to maternal plasma benzodiazepine level was consistently less than 1, and the relative infant dose was always less than 10% of the maternal dose except for ethyl loflazepate, which was only slightly greater than 10% [168]. No abnormalities were noted in the infants.…”
Section: Use Of Benzodiazepines In Special Circumstancesmentioning
confidence: 99%
“…Lorazepam was administered intravenously at a dose of 2.5 mg to pregnant mothers before surgical induction of labour or at the beginning of the second stage of labour. Lorazepam serum concentrations in newborns are similar to those in the maternal serum and rarely exceed the maternal concentrations [40].…”
Section: Transfer Of Lorazepam Across the Human Placentamentioning
confidence: 80%
“…Intranasal lorazepam has more favourable pharmacokinetics than buccal lorazepam in termination seizures in children [38]. Lorazepam freely crosses the human placenta [39,40], and lorazepam poorly migrates into the breast-milk [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Benzodiazepines are excreted only in small amounts in breast milk, so their use could be compatible with breastfeeding. If treatment is beginning postpartum, lorazepam, alprazolam or clonazepam are suggested (Nishimura 2021).…”
Section: Treatment Of Pregnancy-related Anxiety and Perinatal Anxiety...mentioning
confidence: 99%